Cross‐sectional and longitudinal study of the relationship between phase angle and physical function in older adults. Issue 2 (19th January 2023) - Asano, Yujiro; Tsuji, Taishi; Kim, Mijin; Nagata, Koki; Shibuya, Kyohei; Tateoka, Korin; Okura, Tomohiro
Abstract : Aim: Although the validity of the assessment in older adults has been supported by several studies, cross‐sectional and longitudinal relationships between phase angle (PhA) and physical function by sex have not been clarified. This study aimed to examine (i) cross‐sectional relationships and (ii) longitudinal relationships between PhA and physical function in older adults. Methods: A total of 816 and 445 community‐dwelling older adults were included in cross‐sectional and longitudinal analyses, respectively. We evaluated their physical function using grip strength, 5‐repetition sit‐to‐stand test (5‐STS), 5‐meter habitual walk, Timed Up and Go test (TUG), single‐leg balance with eyes open, and sit‐and‐reach test. A multifrequency bioelectrical impedance analyzer was used to determine the PhA at 50 kHz as well as the participants' body composition. Results: In the cross‐sectional analysis, a higher PhA was significantly associated with higher grip strength, sit‐and‐reach, single‐leg balance with eyes open, 5‐STS and lower TUG in women, as well as higher grip strength, single‐leg balance with eyes open, lower 5‐STS and TUG in men, adjusting for age, body mass index and muscle mass. In the longitudinal analysis, there was a significant interaction between PhA and year in the TUG test ( B  = −0.08; 95% CI, −0.136 to −0.025; P  = 0.005) in men. There was no significant interaction between the PhA value and year for the other physical functions. Conclusions: The PhA is a useful indicator for assessing physical function in both older men and women. Furthermore, the PhA may be able to predict mobility limitation in older men. Geriatr Gerontol Int 2023; 23: 141–147 . Abstract : This study examined the relationship between PhA and physical function in community‐dwelling older adults by sex, using cross‐sectional and longitudinal studies. In a cross‐sectional study, a high PhA was associated with better strength, flexibility, balance and lower‐extremity function in women and better strength, balance and lower‐extremity function in men, regardless of age, body mass index and muscle mass. In the longitudinal study, low PhA values predicted mobility limitation in the future, regardless of age in men.